ANALYSIS OF EDUCATION AND TRAINING INFLUENCE ON THE COMPETENCE AND PERFORMANCE OF PARTICIPANTS OF THE MOBILE BRIGADE (BRIMOB) LOCAL POLICE (POLDA RIAU) - Joswa Pernando; Dadi Komardi; Teddy Chandra (International Conference on Business Management and Accounting, 2022)
The purpose of this study was to examine the effect of education and training on the competence and performance of the tamtama mobile brigade (Brimob) of the regional police (Polda Riau). The method used in collecting data in this study was a questionnaire. The sample in this study was the entire population of the regional police Mobile Brigade (Polda Riau) totaling 131 members using the census method. The data analysis technique in this study uses descriptive analysis and Equation Model Structure analysis (SEM) with the help of SmartPLS 3.0 software. The results of the study indicate that education has a very significant impact on competence and performance, training has a very significant impact on competence and performance, and competence has a very significant impact on the performance of the Regional Police Mobile Brigade (Polda Riau).